SYNTHESIS, CHARACTERIZATION, CORROSION INHIBITION OF MILD STEEL BY TWO SCHIFF BASES IN HCL AND DENSITY FUNCTIONAL THEORY STUDIES - Madani, A; Sibous, L; Bentouhami, E (university of el oued/جامعة الوادي, 2021)
In this study, two Schiff bases namely (E,E)-N,N’-biphenyl-4-4’diylbis[1-(furan-2-yl)methanimine] (BEFu) and3-[(Z)-N(4’-aminobiphenyl-4yl)ethanimidoyl]-2-hydroy-6-methyl-4H-pyran-4-one (BEDh) have been synthesized and characterized using UV-visible, FTIR, and NMR techniques. The corrosion inhibition study of BEFu and BEDh was investigated for mild steel corrosion in 1M hydrochloric acid medium using weight loss method, potentiodynamic polarization, EIS techniques, and Density Functional Theory (DFT). The results showed that the inhibition efficiency increasing with concentration and revealing a mixed-type inhibitor of predominantly anodic type. To explain the inhibition abilities of those molecules adsorbed on the mild steel surface, quantum chemical calculations have been performed using DFT. The HOMO and LUMO energies were calculated to determine the global reactivity indexes. The experimental and theoretical results were in good agreement
ARTICLE
Keywords: weight loss method; inhibitor; polarization curves; DFT; HOMO; LUMO